No-Cook Process for Ethanol Production Using Indian Broken Rice and Pearl Millet - Vipul Gohel; Gang Duan (International Journal of Microbiology)
No-cook process using granular starch hydrolyzing enzyme (GSHE) was evaluated for Indian broken rice and pearl millet. One-factor-at-a-time optimization method was used in ethanol production to identify optimum concentration of GSHE, under yeast fermentation conditions using broken rice and pearl millet as fermentation feedstocks. An acid fungal protease at a concentration of 0.2 kg per metric ton of grain was used along with various dosages of GSHE under yeast fermentation conditions to degrade the grain proteins into free amino nitrogen for yeast growth. To measure the efficacy of GSHE to hydrolyze no-cook broken rice and pearl millet, the chemical composition, fermentation efficiency, and ethanol recovery were determined. In both feedstocks, fermentation efficiency and ethanol recovery obtained through single-step no-cook process were higher than conventional multistep high-temperature process, currently considered the ideal industrial process. Furthermore, the no-cook process can directly impact energy consumption through steam saving and reducing the water cooling capacity needs, compared to conventional high-temperature process.